Charm production in charged current deep inelastic scattering at HERA - Abt, Iris; Gangadharan, Dhevan; Masciocchi, Silvia (Journal of high energy physics, 2019)
Charm production in charged current deep inelastic scattering has been measured for the first time in e± pcollisions, using data collected with the ZEUS detector at HERA, corresponding to an...